Compassion, secure flourishing, and organizational commitment of managers - Ford, Mari; Rothmann, Sebastiaan; Van Zyl, Llewellyn Ellardus (Frontiers in Organizational Psychology, 2024)
Compassion is important for facilitating individual well-being and commitment. However, little is known about its importance and function within organizational contexts. This study aimed to assess the associations between compassion for others, experienced compassion, secure flourishing, and organizational commitment within a sample of 390 managers from South Africa. Given that Pommier's Compassion Scale (which was used in this study) was not previously validated in South Africa, the study investigated its factorial validity and measurement invariance across genders. The Compassion Scale, Experienced Compassion Scale, Secure Flourishing Index and Organizational Commitment Scale were administered via an online survey. The results supported a bifactor ESEM Model with one general compassion factor and four specific subscale factors (mindfulness, kindness, indifference, and common humanity). Managers' general compassion and belief in common humanity (a compassion subscale factor) significantly affected their secure flourishing, yet not their organizational commitment. Compassion experienced from others, however, had a strong and significant effect on their secure flourishing and organizational commitment. The results indicate that the Compassion Scale is a valid, gender invariant, and reliable measure of compassion for others, and is suitable for organizational research. Giving and receiving compassion at work has significant benefits for managers and organizations.